The economics of monetary integration - Paul de Grauwe (Oxford Univ. Press, 1997)
The book analyzes the theory of optimum currency areas, concerning the question of whether the European Union constitutes an optimum currency area. The book also deals with the transition towards monetary union and the operation of the future EMU, it discusses how to fix the convertion rates at the start of EMU, the stability pact that should govern fiscal policies in the future EMU, the design and the operational procedures of the European central bank, the relation between the "ins" and "outs"